Comparative Analysis of Codeigniter, Laravel and Ktupad Frameworks: Case Study Online Exam Applications - Wawan Sismadi; Indra; Besar Agung Martono; Titing Widyastuti (Indonesian Journal of Applied Research (IJAR), 2022)
The speed of access to digital information is essential in making decisions, and Google Development requires a data access limit of no more than three seconds. This study analyzes performance, security, and other measurements among three frameworks: CodeIgniter, Laravel, and Ktupad. This research methodology uses digital forensics as a framework for the collection of functions, classes, and rules. In contrast to libraries that are only for a specific purpose, the framework comprehensively regulates how we build applications. Frameworks allow us to build applications faster because we will focus more on the subject matter as developers. SDLC (System Development Life Cycle) consists of 3 stages: Framework Testing, Framework Analysis, and Framework Evaluation. The case study of this research is an Online Exam at Junior High School 242 Jakarta, which was built using CodeIgniter Web Framework, Boostrap, JQuery, Laravel, and Ktupad Web Framework and then compares the three using the Research and Development method with the Extreme Programming (XP) approach. Comparison tool using Web Dev, Apache JMeter, and ZAP OWASP. The results of this study show that the performance values are 1-100 from CodeIgniter 77, Laravel 75, and Ktupad 99, and security values from CodeIgniter Medium, Laravel Medium, and Ktupad Low.